Monitoring System For Premature Baby Weight and Incubator Temperature Using Telegram Messanger With Smart Notificaton - Era Madona; Yulastri Yulastri; Roni Putra; Anggara N; Aditya Wardhani (Politeknik Negeri Padang, 2023)
This research is designed as solution to maximize the automation service to premature baby in smart health concept. The aim of this research built the monitoring system to show the condition of premature baby weight and the incubator temperature using telegram messenger. The incubator in this research using grashof method and some hardware consist of DHT and load cell sensor, Ethernet shield and microcontroller arduino uno. The application in this research applied the Bot fiture from telegram messenger to response message and question. There are two service in the application, first baby weight service and incubator temperature services. Besides these services, the application also have notification service that inform the baby weight under 2,2 kg and the temperature. The experiment result of load cell circuit show error of baby weight measurement is 2,325 % and the bot testing using three commands and notification show the satisfied result.